A perceptual-behavioural approach with non-parametric experimental coefficient for urban parking business design - Moreno Ferrarese (Archives of Transport, 2016)
Transportation science and integrated logistics of passengers in the cities provide a detailed study of the movements both on entry to the urban areas than within them. Parking lots are, very often, places of exchange between the motorized and the pedestrian or cycling mode, or between individual and collective motorized modes. As the modern urban civilization is known by its impetuous car parking expansion it becomes essential to design the parking lots bearing in mind the needs of those who will really use them and not referring to the political lobbies in the city administration. The study of parking lot in terms of business and financial design, planning and management after the construction needs is a more accurate determination of the experimental parameters, which enable choice of the model to minimize the uncertainty of the data that will define the revenues according to the Project Financing procedures.